2012
DOI: 10.1007/s10549-012-2231-1
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy at the time of mastectomy does not increase the risk of lymphedema: implications for prophylactic surgery

Abstract: Women diagnosed with or at high risk for breast cancer increasingly choose prophylactic mastectomy. It is unknown if adding sentinel lymph node biopsy (SLNB) to prophylactic mastectomy increases the risk of lymphedema. We sought to determine the risk of lymphedema after mastectomy with and without nodal evaluation. 117 patients who underwent bilateral mastectomy were prospectively screened for lymphedema. Perometer arm measurements were used to calculate weight-adjusted arm volume change at each follow-up. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Breast cancer-related lymphedema (BCRL) is affecting an increasing number of breast cancer patients with a longer survival rate for the patients [6]. Furthermore, patients who have undergone a mastectomy with axillary lymph node dissection (ALND) have a greater arm-volume and more commonly report www.e-arm.org symptoms of lymphedema, as compared to patients who have received a sentinel lymph node biopsy (SLNB) [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer-related lymphedema (BCRL) is affecting an increasing number of breast cancer patients with a longer survival rate for the patients [6]. Furthermore, patients who have undergone a mastectomy with axillary lymph node dissection (ALND) have a greater arm-volume and more commonly report www.e-arm.org symptoms of lymphedema, as compared to patients who have received a sentinel lymph node biopsy (SLNB) [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Pathologic review confirmed that the IHC-detected cells were morphologically consistent with the patient's contralateral breast carcinomaand there was no evidence of a traumatic origin (e.g., hemosiderin-laden macrophages, multinucleated giant cells, red blood cells, and/or lymphocytes) to suggest that their presence was the result of mechanical cell displacement Bunting et al(48) 5One of the positive lymph nodes was positive only by cytokeratin staining, three were micrometastases, and one was a macrometastasis. Two of the five patients with positive SLNs underwent completion axillary lymph node dissection, but no further lymph nodes were positive in either of those patients Miller et al(49) 1Occult invasive cancer had a micrometastasis to the SLNB Kuwajerwala et al…”
mentioning
confidence: 99%
“…We have found no studies for comparison that are similar to ours that assess the lymphatic circulation in the immediate pre- and postsurgical period of patients submitted to SLNB. Patients submitted to prophylactic mastectomy on whom SLNB was performed showed no significant increase in the risk of developing lymphedema 61. Further studies using early and delayed postsurgery LS imaging should be conducted to identify the actual damage from SLNB to the lymphatic flow, especially when combined with more extensive breast surgery, including oncoplastic surgery.…”
Section: Discussionmentioning
confidence: 99%